Case report: Successful treatment with contezolid in a patient with tuberculous meningitis who was intolerant to linezolid - Xu, Zhe; Zhang, Jing; Guan, Tingting; Wan, Guichuan; Jiang, Chao; Lang, Linchuan; Wang, Lianzhi (Frontiers in Medicine, 2023)
Tuberculous meningitis (TBM) is the most common form of central nervous system tuberculosis (TB) and the most severe form of extrapulmonary TB. It often presents with non-specific symptoms initially and has a high mortality and disability rate. With good central nervous system penetration, linezolid is recommended for treating drug-resistant, severe, or refractory tuberculous meningitis in China. Despite the benefits of linezolid on TBM treatment, the adverse effects of longterm therapy, such as myelosuppression, peripheral neuritis, and optic neuritis, are notable and can be severe and even life-threatening, leading to discontinuation and compromising treatment expectations. Contezolid is a novel oxazolidinone antibacterial agent approved by the National Medical Products Administration of China in 2021, which has a more favorable safety profile than linezolid in terms of myelosuppression and monoamine oxidase inhibition. Here we first report a case of TBM in a patient who was intolerant to antituberculosis treatment with linezolid and achieved good efficacy and safety results after the compassionate use of contezolid. Given the widespread use of linezolid in TB treatment and the potential risks for long-term use, multi-center prospective controlled clinical trials in TB and TBM patients are needed to investigate the appropriate use of contezolid further.